#1**0 **

The line x = -3 goes through point C on the triangle. This means point C stays the same after the reflection.

Then just translate it 4 units right and 1 unit up:

(-3 + 4, 0 + 1)

C" = (1, 1)

Point A after the reflection will be 4 units to the right. This is because the line of reflection is vertical, and point A is 2 units left of the line.

(-5 + 4, 2)

A' = (-1, 2)

Then translate it just like you did for point C:

(-1 + 4, 2 + 1)

A" = (3, 3)

Finally, you can do the same thing in A for point B:

(-6 + 6, -1)

B' = (0, -1)

(0 + 4, -1 + 1)

B" = (4, 0)

Let me know if you have any questions.

Logarhythm May 25, 2022